2021
DOI: 10.1021/acsami.1c01144
|View full text |Cite
|
Sign up to set email alerts
|

Facet Engineering of Bismuth Molybdate via Confined Growth in a Nanoscale Template toward Water Remediation

Abstract: Certain nanomaterials can filter and alter unwanted compounds due to a high surface area, surface reactivity, and microporous structure. Herein, γ-Bi2MoO6 particles are synthesized via a colloidal hydrothermal approach using organically modified Laponite as a template. This organically modified Laponite interlayer serves as a template promoting the growth of the bismuth molybdate crystals in the [010] direction to result in hybrid Laponite–Bi2MoO6 particles terminating predominantly in the {100} crystal facets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 66 publications
(114 reference statements)
3
40
0
Order By: Relevance
“…To promote the separation and transportation of photoinduced charge carriers, Type-II, Z-scheme or p-n heterojunctions are often introduced to the composite photocatalysts to prolong the lifetime of charge carriers so that more electrons can take part in the CO 2 reduction reaction (Jiang et al, 2020;Li S. et al, 2021;Wu et al, 2021). Since CO 2 reduction can only take place on the surface active sites, many recent researches focus on crystal facet engineering in order to maximize the exposure of most active facets (Kong et al, 2018;Jatav et al, 2021). Besides, decreasing the thickness of 2D materials to ultrathin-nanoscale or even atomic layers can endow ultrafast transportation of charge carriers from interior to the surface of photocatalysts along with large exposure of active sites to boost CO 2 adsorption and activation (Han et al, 2021;Teh et al, 2021).…”
Section: Photocatalytic Co 2 Reductionmentioning
confidence: 99%
“…To promote the separation and transportation of photoinduced charge carriers, Type-II, Z-scheme or p-n heterojunctions are often introduced to the composite photocatalysts to prolong the lifetime of charge carriers so that more electrons can take part in the CO 2 reduction reaction (Jiang et al, 2020;Li S. et al, 2021;Wu et al, 2021). Since CO 2 reduction can only take place on the surface active sites, many recent researches focus on crystal facet engineering in order to maximize the exposure of most active facets (Kong et al, 2018;Jatav et al, 2021). Besides, decreasing the thickness of 2D materials to ultrathin-nanoscale or even atomic layers can endow ultrafast transportation of charge carriers from interior to the surface of photocatalysts along with large exposure of active sites to boost CO 2 adsorption and activation (Han et al, 2021;Teh et al, 2021).…”
Section: Photocatalytic Co 2 Reductionmentioning
confidence: 99%
“…Laponite-RD (Lap) is a magnesiosilicate smectite clay of ∼25 nm diameter and 0.92 nm thickness, which can be easily modified due to its high surface area and cation-exchange capacity. In previous studies, surfactant-modified Lap has been shown to be a useful template for colloidal nanoparticle synthesis in both exfoliated and pillared states. The latter tends to lead to the growth of 2D materials with reduced thickness due to the impregnation of the interlayer with nanomaterial precursors. ,, It was also observed that templating the growth of Bi 2 MoO 6 with surfactant-pillared Lap promoted crystal growth along the [010] direction …”
Section: Introductionmentioning
confidence: 99%
“…31,32,34 It was also observed that templating the growth of Bi 2 MoO 6 with surfactant-pillared Lap promoted crystal growth along the [010] direction. 33 The goal of this study is twofold. First, this represents an effort to achieve templated growth on the basal surface of laponite without cationic surfactants or pillaring of the clay.…”
Section: ■ Introductionmentioning
confidence: 99%
“…33−35 Interestingly, in the case of Bi 2 MoO 6 (BMO), self-assembly of pillared Lap template particles resulted in micrometer-sized particles with surfaces terminating in predominantly {100}-facets, which were found to be effective at quickly sequestering molecular dyes. 36 In addition, their reuse was achieved by photocatalytic degradation of an aqueous particle dispersion following dye adsorption. The characteristics of high adsorption capacity, fast adsorption kinetics, and reuse by photocatalytic degradation motivated further efforts to optimize this system for a real application.…”
Section: ■ Introductionmentioning
confidence: 99%